Modulation of feedback-related negativity during trial-and-error exploration and encoding of behavioral shifts - Sallet, Jérôme; Camille, Nathalie; Procyk, Emmanuel (Frontiers in Neuroscience, 2013)
Expectations regarding outcomes of potential decisions to be taken, detection and evaluation of the actual outcomes are of crucial importance to influence behavioral choices. The feedback-related negativity (FRN) is a mid-frontal event-related potential (ERP) recorded in various cognitive tasks in association to onset of sensory feedback signalling decision outcome. In the present study we asked human subjects to search by trial and error which of five visual targets was associated with a correct feedback. After exploration and discovery of the correct target, subjects could repeat their correct choice until the onset of a signal to change (SC) indicative of a new search. Our goals were to resolve some of the debates regarding the sensitivity of the FRN to positive and negative feedback, and to varying levels of outcome expectancy. We also tested whether the FRN would be elicited by an instruction cue indicating the need for behavioural adjustment. Analyses showed that the FRN was modulated by both negative and positive prediction error (RPE), i.e. the discrepancy between the probability to be correct and the occurrence of the actual feedback. However, the P300, a mid-parietal ERP, was only modulated by the probability of the positive feedback. Thus we concluded that FRN modulation was not driven by a modulation of the P300. Finally, we found the SC also elicited an FRN-like potential on the frontal midline electrodes, which was not modulated by the probability of that event. Altogether these results suggest that the FRN may reflect mechanisms that evaluate events (outcomes, instruction cues) that signal the need to engage different adaptive action.